Uterine Involvement in Klippel–Trenaunay Syndrome: A Rare But Relevant Event. Review of the Literature - Cucinella, Gaspare; Di Buono, Giuseppe; Geraci, Girolamo; Ricupati, Federica; Gullo, Giuseppe; Maienza, Elisa; Romano, Giorgio; Bonventre, Giulia; Amato, Giuseppe; Romano, Giorgio; Buscemi, Salvatore; Agrusa, Antonino (Frontiers in Surgery, 2022)
Introduction Klippel Trenaunay syndrome is a rare vascular congenital disorder characterized by the classical triad of port-wine stains, abnormal overgrowth of soft tissues and bones and vascular malformations. The involvement of the genitourinary tract and of the uterus in particular is extremely infrequent, but relevant for the possible consequences Methods We performed an extensive review of literature using the Pubmed, Scopus and ISI web of knowledge database to identify all cases of KTS with uterine involvement. The search was done using the MeSH term “Klippel-Trenaunay syndrome” AND “uterine” OR “uterus”. We considered only publications in English language with no limits of time. We selected a total of 11 records of KTS with uterine involvement considering also those affecting pregnant women Results Klippel-Trenaunay syndrome was described for the first time in 1900 in two patients with hemangiomatous lesions of the skin associated with varicose veins and asymmetric soft tissue and bone hypertrophy. Uterine involvement is a rare condition and can cause severe menorrhagia. Diagnosis is based on physical signs and symptoms. CT scans and MRI are first choice exams to evaluate both the extension of the lesion and infiltration of deeper tissues before treatment. The management of Klippel-Trenaunay syndrome should be personalized and makes use of careful diagnosis, prevention and treatment of complications. Conclusion The syndrome of Klippel-Trenaunay is a rare vascular malformation with a wide variability of manifestations. There are no univocal and clear guidelines that suggest the most adequate monitoring of the possible complications of the disease. Treatment is generally conservative but in presence of recurrent bleeding, surgery may be needed.